2018
DOI: 10.1242/dmm.029082
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila junctophilin gene is functionally equivalent to its four mammalian counterparts and is a modifier of a Huntingtin poly-Q expansion and the Notch pathway

Abstract: Members of the Junctophilin (JPH) protein family have emerged as key actors in all excitable cells, with crucial implications for human pathophysiology. In mammals, this family consists of four members (JPH1-JPH4) that are differentially expressed throughout excitable cells. The analysis of knockout mice lacking JPH subtypes has demonstrated their essential contribution to physiological functions in skeletal and cardiac muscles and in neurons. Moreover, mutations in the human JPH2 gene are associated with hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 86 publications
(115 reference statements)
0
18
0
Order By: Relevance
“…Junctophilin, overexpressed in the field‐derived pyrethroid‐resistant WCR population, is a protein commonly found in human neurons, where it is involved in coupling membrane neurotransmitter receptors and intracellular channels 88 . A study showed that a junctophilin gene from Drosophila melanogaster Meigen is functionally equivalent to mammalian homologues and that flies with altered junctophilin expression also have marked neuronal alterations 89 . The predicted E3 ubiquitin‐protein ligase and neprilysin, overexpressed in the laboratory‐selected pyrethroid‐resistant WCR populations, also play a role in the nervous system of insects.…”
Section: Discussionmentioning
confidence: 99%
“…Junctophilin, overexpressed in the field‐derived pyrethroid‐resistant WCR population, is a protein commonly found in human neurons, where it is involved in coupling membrane neurotransmitter receptors and intracellular channels 88 . A study showed that a junctophilin gene from Drosophila melanogaster Meigen is functionally equivalent to mammalian homologues and that flies with altered junctophilin expression also have marked neuronal alterations 89 . The predicted E3 ubiquitin‐protein ligase and neprilysin, overexpressed in the laboratory‐selected pyrethroid‐resistant WCR populations, also play a role in the nervous system of insects.…”
Section: Discussionmentioning
confidence: 99%
“…Junctophilin, overexpressed in the field-derived pyrethroid-resistant WCR population, is a protein commonly found in human excitable cells such as neurons where it is involved in coupling membrane neurotransmitter receptors and intracellular channels (Landstrom et al 2014). A study showed that a junctophilin gene from fruit fly Drosophila melanogaster Meigen is functionally equivalent to mammal homologues and that flies with altered junctophilin expression also have marked neuronal alterations (Calpena et al 2018). The predicted E3 ubiquitin-protein ligase and neprilysin, overexpressed in the lab-selected pyrethroidresistant WCR populations, also play a role in the nervous system of insects.…”
Section: Discussionmentioning
confidence: 99%
“…HD is caused by poly-glutamine (polyQ) expansions in the Huntingtin ( HTT ) gene. Using a fly model of HD in which mutant Huntingtin protein was overexpressed in the eye causing an age-dependent rough eye phenotype, Calpena et al found that knock-down of junctophilin ( jp ) enhances this phenotype while overexpression of jp suppresses this defect [ 217 ]. In the same paper, the authors noted that ubiquitous knock-down of jp causes bristle and wing vein phenotypes that are reminiscent of Notch LOF defects, and further showed that jp genetically interacts with Delta mutants.…”
Section: Notch Signaling As a Modifier Of Neurodegenerative Diseasmentioning
confidence: 99%